Diseño de arreglos de antenas logarítmicas usando algorítmos genéticos - Gómez Paredes, Juan Carlos; Gómez Vargas, Manuel Fernando; Zarate Arcos, Jaime (Ingeniería, 2001)
The LPDA antennas are employed widely, especially in the VHF and UHF bands. They have a lower gain, and may be increased by combining several antennas in an array. The arrays are characterized by the location of the elements with respects to the others are defined by angles which determine in conjunction with the dimensions of the elements, the gain of the system. By optimizing these angles and the dimensions of the elements we also optimize the gain and size of the antenna. The process of optimization described above may be speeded up by employing Genetic Algorithms.